Extensão na educação profissional e técnica de nível médio do Instituto Federal do Amazonas: formação humana integral e reflexo social - Peres, Aline Neves (2020)
The extension activities, along with teaching and research areas construct formative contributions to their participants, which involve the aspects of integral human formation and the social impact. The present work is part of the research line Organization and Memories of Pedagogical Spaces in Technological and Professional Education. In this research line, we seek to identify the directions that guide the implementation of extension activities at Federal Institute of Amazonas (IFAM) and their contributions to the integral human formation of students from Technical and Professional Education at Secondary School (EPTNM). This work is a field study, carried out with students of Secondary School and teachers who are participants of the Program of Extension Scholarships of Federal Institute of Amazonas, in 2019. Applying qualitative research, we used the dialectical approach method, with steps of bibliographic research, documentation, and field study. The technique of semistructured interview was conducted in a sampling of 10 students and 6 teachers, who are participants in the extension projects, in addition to the systematic observation during the follow up of the activities. We employed the technique of contents analysis for the processing and interpretation of data. As results, we highlight the contributory aspects in the improvement and learning of skills in academic, professional, and personal context as well as the awakening to social participation initiatives. However, some challenges are still present, namely in the articulation involving teaching and research, or in the development of interdisciplinary activities in extension practices. As an educational product, we created a booklet that has the objective to encourage the participation and to orientate about the possibilities of future developments in extension projects.